Assistance to Wonopringgo Village Towards a Women-Friendly and Child-Caring Village: Pendampingan Desa Wonopringgo Menunuju Desa Ramah Perempuan dan Peduli Anak - Hayudya Ningtyas, Wulan; M. Fathurrozak, M. Fathurrozak; Rif'iyati, Dian (Dharmahita: Journal of Community Service and Development, 2024)
Women and children represent a significant portion of Indonesia's population, making up about 65% or two-thirds of the total population. This demographic is concentrated in 74,961 villages across the country. Optimizing the potential of women and children through empowerment and protection is vital for national development, as outlined in Presidential Regulation No. 18 of 2020 on the National Medium-Term Development Plan for 2020-2024. The KKN 58 group 06 from UIN K.H. Abdurrahman Wahid Pekalongan, in collaboration with the Women's Empowerment and Child Protection Service, conducted outreach in Wonopringgo Village to emphasize the importance of creating a Women-Friendly and Child-Caring Village. The aim was to ensure that the community, particularly women and children, can actively participate in village development and secure their rights. The socialization activities provided knowledge and understanding of what a Women-Friendly and Child-Caring Village entails and its benefits, striving to integrate gender perspectives and children's rights into village governance, development, and empowerment processes.